Individualism and Collectivism at Work in an Era of Deindustrialization: Work Narratives of Food Delivery Couriers in the Platform Economy - Stewart, Paul; Shanahan, Genevieve; Smith, Mark (Frontiers in Sociology, 2020)
Abstract Supposedly emblematic of digital capitalism, the rise of the gig economy is frequently taken as a cypher for the developing deindustrialisation of western societies. It is tempting to interpret the shift of manufacturing jobs to the global south and their replacement with service sector jobs as a one-way street, leading to the demise of decent work and the rise of work characterised by precarity, low pay, low skill and a non-unionised workforce. However, the reality is inevitably more complex. In the first place, pessimism may be attributed to a rose-tinted view of the experience of former industrial employment in the global north resulting from a questionable assumption about the nature of the jobs that occupied most people in former industrial societies. Certainly, deindustrialisation is not leading to ‘de-working’, that is, working less for the same money. . Our evidence derives from qualitative interviews with gig workers in the food delivery sector in a number of European countries. We highlight the extent to which couriers profess a variety of understandings of the character of platform economy labour processes. A range of narratives emerge including platform work as leisure, as economic opportunity, and as collectivist labour. Moreover, individuation, attendant upon the character of the physical labour process, did not lead in any straightforward way to individualism in social labour processes – contrary to our expectations, we in fact witnessed forms of collectivism. Counterintuitively we found that these forms of collectivism were driven by the nature of the work itself. Given platform apps’ external control, the gig economy spatially separates workers while at the same time requiring cognition of colleagues’ collective work and labour process. Notwithstanding structural processes separating workers-in-work, platforms also witness the instantiation of forms of collectivism. Deindustrialisation is neither the end to collectivism nor trade unionism. Rather than post-work, then, we explore the problematics of plus work and variant collectivisms.